(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article provides a comparative analysis of financing the construction of public roads of regional, intermunicipal and local significance. A vision for improving the financial provision of road construction through the introduction of agreements on the provision of other interbudgetary transfers for three budget cycles has been defined.